Magnetic hydrogels with ordered structure for biomedical applications - Xue, Le; Sun, Jianfei (Frontiers in Chemistry, 2022)
Magnetic hydrogels composed of hydrogel matrices and magnetic nanomaterials have attracted widespread interests. Thereinto, magnetic hydrogels with ordered structure possessing enhanced functionalities and unique architectures, show tremendous advantages in biomedical fields. The ordered structure brought unique anisotropic properties and excellent physical properties. Furthermore, the anisotropic properties of magnetic ordered hydrogels are more analogous to biological tissues in morphology and mechanical property, showing better biocompatibility and bioinducibility. Thus, we aim to systematically describe the latest advances of magnetic hydrogels with ordered structure. Firstly, this review introduced the synthetic methods of magnetic hydrogels focus on constructing ordered structure. Then, their functionalities and biomedical applications are also summarized. Finally, the current challenges and a compelling perspective outlook of magnetic ordered hydrogel are present.